Pragmatic estimates of the proportion of pediatric inpatients exposed to specific medications in the USA. (23rd May 2013) - Feudtner, Chris; Dai, Dingwei; Faerber, Jennifer; Metjian, Talene A.; Luan, Xianqun
ABSTRACT: Purpose: To provide pragmatic national estimates of the proportion of hospitalized pediatric patients exposed to specific drugs in the USA. Methods: We used Premier Perspective Database and the Pediatric Health Information System data including specific drug exposures of 1.15 million inpatients <18 years old in 411 general and 52 children's hospitals throughout the USA in 2006, extrapolating this information into the probability‐based Kids' Inpatient Database, which has demographic and clinical characteristics but no drug exposure data. We used a multivariable stratified resampling (MSR) technique to estimate the proportion of drug exposure for the 700 most commonly used drugs and performed additional stability and sensitivity analyses for 19 drugs. Results: The estimated proportion of pediatric inpatients exposed to specific drugs in 2006 ranged from high levels such as that of acetaminophen (17.36; 95%CI: 17.32, 17.41) to rare exposures such as bosentan (0.0018; 95%CI: 0.0013, 0.0023). Additional analyses for 19 drugs revealed that the MSR estimates were close to estimates generated by multivariable multiple imputation, with a maximum absolute difference of 0.03 for acetaminophen (17.36 vs. 17.33) and famotidine (1.90 vs. 1.93), and that even with 50% of the hospitals removed at random, the proportion estimates did not vary by more than 2.5‐fold at the upper 97.5 percentile. Conclusions: These pragmatic national estimates of the proportion of pediatric inpatient drug exposures, generated using an MSR technique, provide a context for interpretation of drug‐related adverse event reports and prioritization of pediatric pharmacology research. © 2013 The Authors. Pharmacoepidemiology and Drug Safety published by John Wiley & Sons, Ltd.